2021
DOI: 10.3390/rs13040801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Abandoned Jujube Fields Using Multi-Temporal High-Resolution Imagery and Machine Learning

Abstract: The jujube industry plays a very important role in the agricultural industrial structure of Xinjiang, China. In recent years, the abandonment of jujube fields has gradually emerged. It is critical to inventory the abandoned land soon after it is generated to adjust agricultural production better and prevent the negative impacts from the abandonment (such as outbreaks of diseases, insect pests, and fires). High-resolution multi-temporal satellite remote sensing images can be used to identify subtle differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The 224th regiment, the study area selected for this experiment, is located north of National Highway 315 at the crossroads of Pishan County and Moyu County in Hotan Region, on the southern edge of the Great Taklamakan Desert in Xinjiang, China (Li et al, 2021). The total land area is 234,751 km 2 and the terrain slopes from the southwest to the northeast.…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The 224th regiment, the study area selected for this experiment, is located north of National Highway 315 at the crossroads of Pishan County and Moyu County in Hotan Region, on the southern edge of the Great Taklamakan Desert in Xinjiang, China (Li et al, 2021). The total land area is 234,751 km 2 and the terrain slopes from the southwest to the northeast.…”
Section: Study Areasmentioning
confidence: 99%
“…Satellite remote sensing is primarily used for monitoring broad areas, but it cannot provide images with sufficient spatial resolution and the images are susceptible to weather conditions (Bendig et al, 2015;You et al, 2022). In addition, the progressive improvement of UAV technology has made feasible its combination with hyperspectral and multispectral technology for agricultural disease monitoring, providing a reference for accurate crop disease monitoring and to guide remedial management (Adao et al, 2017;Li et al, 2021). For instance, UAV hyperspectral remote sensing can monitor a broad area with high precision, efficiency, and continuity, and accomplish the fusion of UAV multisource remote sensing imagery and target extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in ResNet, we made modifications and additions to the sequential model structure, ultimately achieving positive outcomes. Xingrong Li et al identified abandoned jujube orchards with an accuracy of 91.1% using multi-temporal high-resolution imagery and machine learning techniques, showing a significant enhancement in accuracy compared to other moderate-resolution satellite images [60]. However, our experimental approach, employing CNN-based models, clearly demonstrated superior performance compared to these established traditional methods and previous research findings.…”
Section: Discussionmentioning
confidence: 56%
“…Morell-Monzó et al [12] used Sentinel-2 and airborne imagery to map land abandonment (citrus cultivation) in fragmented landscapes in Spain, applying the Random Forest algorithm for the classification of pixels. Li et al [16] applied field-based and pixel-based classification of field boundaries to estimate the percentage of abandoned jujube fields with multi-temporal high spatial resolution satellite images (Gaofen-1 and Gaofen-6) and the Random Forest algorithm.…”
Section: Introductionmentioning
confidence: 99%